2017
DOI: 10.4102/hsag.v22i0.981
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of registered nurses caring for patients with an open abdomen in an intensive care unit in Gauteng

Abstract: Intra-abdominal hypertension (IAH)AbdominalEthical principles and measures of trustworthiness were adhered to throughout the research study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…based on the investigator point of view, these findings may be interpreted by the older nurses' reluctance to work in ICUs and CCUs, as well as the fact that senior nurses in the upper age categories fulfill administrative roles. These findings agree with the study done by Mobed et al (12) , and was contradicted with Chipu et al (13) .…”
Section: Demographic Characteristic Of the Studied Nursessupporting
confidence: 79%
“…based on the investigator point of view, these findings may be interpreted by the older nurses' reluctance to work in ICUs and CCUs, as well as the fact that senior nurses in the upper age categories fulfill administrative roles. These findings agree with the study done by Mobed et al (12) , and was contradicted with Chipu et al (13) .…”
Section: Demographic Characteristic Of the Studied Nursessupporting
confidence: 79%
“…We cannot make any conclusion regarding the only female in the study. Though South Africa is known to have a significant amount of penetrating trauma, this study group was all blunt traumatic aortic injuries in keeping with an aortic theme [27][28][29][30]. In contrast, the age group in the study was slightly older than our trauma population, as demonstrated in other local studies [23][24][25][26]31].…”
Section: Discussionmentioning
confidence: 81%
“…This has resulted in misinterpretations and misunderstanding of the concepts ‘patient care’ and ‘self-care’. Some nursing professionals regard self-care as being selfish, and this results in stress, depression, feelings of worthlessness and feelings of helplessness [ 12 ]. Analysing the concept of self-care will thus enhance understanding of the concept, its use and the practice of self-care activities amongst nursing professionals.…”
Section: Introductionmentioning
confidence: 99%